Regional Government Strategy in Developing Small and Medium Industries (IKM) - Abdul Hamid, Najmah Najmah; Abdurrahman, H.; Dermawan, M. Ariy (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Small and medium industries have an important role in driving overall economic growth. Industrial development, especially small industry, is aimed at becoming a high-quality role in the economy, so that it is able to compete both domestically and abroad. The aim of this research is to determine local government strategies in developing small and medium industries (IKM). Mataram City Regional Regulation Number 15 of 2016 concerning the formation and composition of Mataram City regional apparatus. The problem with the research is that there is still minimal information for SMEs to access capital in banking institutions, there is no supporting facilities such as machine tools. The location in this research is the Department of Industry, Mataram City SME Cooperative as the research object. This type of research uses descriptive with a qualitative approach. The data collection techniques that researchers used in this research were interviews, observation, documentation. Data analysis techniques use data reduction, data display, and drawing conclusions. The results of this research show. The strategy implemented by the Mataram City SME Cooperative Industrial Service was carried out well even though it was not 100% realized. Supporting factors provided by the Mataram City SME Cooperative Industrial Service. City SME cooperative industry. Providing training guidance, preparing budgets and providing facilities through cooperatives or banking institutions.